Astronomy Development since Antiquity to Islamic Civilization from the Perspective of Islamic Historiography - Abdul Niri, Mohammaddin; Jamaludin, Mohd Hafiz; Mohd Nawawi, Mohd Saiful Anwar; Ahmad Zaki, Nurulhuda; Abdul Wahab, Raihana (Journal of Al-Tamaddun, 2023)
Modern science historiography views astronomy development since antiquity solely on human interaction with nature. Such a secular evolutionary view is derived from the positivistic paradigm. In contrast, the Islamic science historiography perspective explains astronomy development since antiquity primarily based on revealed knowledge, while the scientific method is employed accordingly. Even so, there are differences among scholars in elucidating Islamic science historiography which is classified into two dimensions. The first dimension focuses on the philosophical aspects that underline the historical narrative and the second dimension prioritises scientific evidence. The question is how these differences could be reconciled so that the historical narrative of astronomy development that emerged from modern science historiography would be more coherent with Islamic science historiography. Therefore, this library study was conducted using data collection based on the documentation method and a content analysis method was employed for data analysis. As a result, the Priority Principle from fiqh al-awlawiyyat as a strategic locus to reconcile the differences in Islamic science historiography was identified. The principle prioritises the role of Allah, the prophets and the revelations according to Shariah and the scientific method is used suitably. It is also crucial to be emphasised in addressing the secular evolutionary view that underlie astronomy development. It is thus concluded that astronomy development from antiquity to Islamic civilization can be marked as starting from the time of Prophet Adam and will be over at the end of time.